A self-adaptive semiconductor–liquid junction for highly active and stable solar water splitting. Issue 38 (31st August 2022) - Sun, Huanhuan; Hua, Wei; Liang, Shiyu; Li, Yueying; Wang, Jian-Gan
Abstract : A self-adaptive semiconductor–liquid junction with reduced interface recombination and fast water oxidation kinetics is constructed via a novel and efficient reconstruction strategy for highly active and stable solar water splitting. Abstract : Constructing a semiconductor–liquid junction (SCLJ) with efficient charge transfer and excellent anti-photocorrosion is crucial yet challenging for photoelectrochemical (PEC) water oxidation. Herein, we propose an effective surface reconstruction strategy to create a self-adaptive SCLJ for significantly enhancing the PEC activity and stability of BiVO4 photoanodes. It is revealed that a low-valence metal oxide ( e.g., NiFeO x ) serrated cocatalyst could be in situ transformed into a uniform and seamless oxygen-vacancy-rich metal (oxy)hydroxide nanolayer during the initial PEC test cycles. Such an intriguing reconstruction creates a self-adaptive SCLJ to promote hole trapping/migration at the semiconductor/cocatalyst junction and improve the water oxidation kinetics as well as photocorrosion resistance at the electrode/electrolyte interface. Remarkably, the self-adaptive SCLJ enables BiVO4 to show an impressive photocurrent density of 5.1 mA cm −2 at 1.23 V vs. RHE and superior working durability over 30 h. This study provides a fundamental insight on designing a self-adaptive SCLJ for highly efficient PEC water electrolysis.